Smart parking tying dynamic costing method - Emmanuel Ufiteyezu (Fakulti Kejuruteraan ,UKM,Bangi., 2023)
ABSTRACT The solicitation of smart cities will increase unexpectedly with the rapid increase in IoT infrastructure. Smart City idea notably going up to city lifecycle. Parking is an important part of smart cities yet parking is a difficult process because there isn’t a good way to pay for it or find a spot in the existing system. The number of vehicles in our city is increasing day by day due to which there is an immediate need for a good parking system. The focal point of this paper is to manage parking lots by including dynamic costing methods incorporated in a novel iOS apps-based implementation for smart cities’ demands, which permits a user or driver to make an option for pricing the desired slot and booking the desired slot based on costing in that lot. That means, that developed iPark proposes innovative costing strategies that permit the making of additional parking profits and the rational ordering of parking transportation through parking lots. This paper additionally focuses on reducing the searching time for determining the parking lot using our proposed method, namely, the booking method. From the results, we can see that our proposed method increases profits as well as utilized resources properly compared to the existing methods.